Nutraceuticals in Alternative and Underutilized Fruits as Functional Food Ingredients: Ancient Species for New Health Needs - Donno, Dario (Alternative and Replacement Foods, 2018)
A diet containing high levels of fruit has been associated with a lowered risk of chronic diseases as, in addition to their vitamin and mineral content, they also contain various compounds with health-protective effects, in particular antioxidant and antiinflammatory compounds. Wild plant species are of interest to the food industry because of their ability to replace synthetic chemicals and nutraceuticals; however, the nutritional, economical, and sociocultural values of some neglected and underutilized natural resources have not yet been fully exploited. Some of these less well-known and underutilized fruits, which have the potential to provide novel sources of health-promoting agents, are presented in this chapter (i.e., Asimina triloba (L.) Dunal, Crataegus azarolus L., Lycium barbarum L., Morus nigra L., and Amelanchier canadensis (L.) Medicus). Underutilized fruits could represent an opportunity for growers to gain access to these special markets where consumers place emphasis on high contents of nutrients that are capable of preventing degenerative diseases. The development of specific horticultural models for nutraceutical fruit production could be an interesting opportunity to obtain a highly standardized raw material for fresh or derived products.